(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
The integration of clinical microbiology into forensic medicine and toxicology has revolutionized investigative method ologies, enhancing the precision of criminal investigations. This review examines the role and impact of clinical micro biology in forensic contexts, focusing on its applications, technological advancements, challenges, ethical considerations, and future prospects. Forensic microbiology has proven invaluable in various forensic investigations, such as identifying pathogens in unex pected deaths, analysing soil microbiomes to infer crime scene geolocations, and utilizing the human microbiome for individual identification. Advances in next-generation sequencing, artificial intelligence, and machine learning have significantly enhanced the capabilities of forensic microbiology, enabling faster and more precise analyses. These tech nologies facilitate a deeper understanding of microbial evidence, contributing to more accurate forensic conclusions. However, the field faces challenges, including the need for standardized methodologies and protocols, rapid pathogen identification, and handling complex microbial ecosystems. Ethical considerations, particularly regarding the privacy of microbiome data and its legal interpretation, are also pivotal. Future research directions emphasize developing rapid on-site testing methods, expanding microbial databases, and establishing robust ethical frameworks for microbiology’s use in forensic science. These advancements are anticipated to further refine forensic microbiological methods, ensuring their responsible and effective application in legal investiga tions. In summary, the integration of clinical microbiology into forensic medicine and toxicology marks a significant ad vancement in forensic science. It offers enhanced capabilities in crime scene analysis and pathogen identification, while posing challenges that require careful consideration and ongoing research. The continued evolution of this field prom ises to significantly contribute to the efficacy and integrity of forensic investigations.